Radical renovations inspiring architectural makeovers - Browne, Beth (Images Publishing., 2013)
Radical Renovations presents more than 50 outstanding examples of adaptive reuse in residential and commercial architecture, wherein existing buildings have been dramatically transformed with truly stunning results. Australian content